The Influence of Islamic Law Principles on Human Resource Management - Mukhsinuddin, Mukhsinuddin; Efendi, Sumardi (Jurnal Ilmiah Teunuleh, 2025)
Human Resource Management has an important role in improving the effectiveness and productivity of an organization. In Islam, human resource management is not only oriented to profit, but also to ethical values and justice. Islamic legal principles, such as justice (al-'adl), amanah, deliberation (shura), and ihsan, provide moral guidance in managing the workforce. This study aims to analyze the influence of Islamic legal principles on human resource management and how these principles can be implemented in organizations. This study uses a library research method with a descriptive-analytical approach. Data is collected from various literature sources, such as fiqh books, scientific journals, and books that discuss Islamic law and human resource management. The results of the study show that the application of Islamic principles in human resource management contributes to the creation of a fairer and more harmonious work environment. However, this implementation still faces challenges, such as lack of understanding and resistance to change. Therefore, education, regulation, and a gradual approach are needed to adopt Islamic principles in human resource policy. With the right strategy, Islamic law can be the basis for a more equitable and sustainable human resource management system.